Education On Simplifying Digital-Based Village Administrative Affairs - Nuraini , Rini; Harsya, Rabith Madah Khulaili; Arjulayana , Arjulayana; Meiyenti , Ira; Agustina , Ika (Universitas Pahlawan Tuanku Tambusai, 2024)
When the author carried out service for one month, namely in Pekalangan village for two weeks and in Pekalangan village for two weeks, the author discovered exactly the same problem, namely the complexity of managing administration in rural areas. After that, the author held discussions with other colleagues and found a solution to simplify the village administration program. As a result, the authors agreed to propose creating a website in each village with the main aim of making it easier for village residents to manage administration. The research results show 1). When observing for two weeks in each of the villages of Bojong Loa and Pakalaang, the author found similar problems, namely the difficulty of managing administration in both villages. 2). The author suggests a solution for village officials to form an IT team, coordinating with local governments, in this case the Tanggerang city government and Cirebon Regency, so they can create a website. 3). The village website functions to make it easier for rural communities to take care of administrative matters such as administering KK, KTP, KIP, KIM, making it easier for people to get information, and as a form of transparency in the use of village funds. 4). The village website has been implemented and is successful in several villages such as Kertamulya village and has succeeded in making it easier for village residents to take care of administration.